64 Utc Demonstrates Improved Tendon Matrix Integrity After Plantaris Excision. (5th September 2014) - Masci, Lorenzo; Alfredson, Hakan
Abstract : Introduction: The plantaris tendon is increasing recognised as an important factor in midportion Achilles tendinoapathy. Recent cadveric 1 and histological studies 2 lend support to the theory that the plantaris tendon may be involved in the aetiology and/or the pathogenesis of midportion Achilles tendinopathy. In addition, a recent innovative surgical procedure for Achilles tendinopathy, which involves excision of plantaris tendon in addition to scraping of the Achilles tendon, has demonstrated good clinical outcomes. 3 Nevertheless, there is a paucity of studies investigating the outcomes of surgery with validated outcome measures. Recently, a novel imaging modality, Ultrasound Tissue Characterisation (UTC), has been used to quantify tendon matrix integrity and has been shown to be reliable and valid 4, 5 . Unlike 2D ultrasound and Colour Doppler, UTC objectively quantifies grey-scale tendon matrix changes into 4 different echotypes related to tendon integrity. Namely, type I (green) and II (blue) represents organised matrix; type III (red) and IV (black) represents disorganised matrix. The aim of this study was to investigate the outcomes of an innovative surgical procedure for Achilles tendinopathy including excision of plantaris using validated clinical (VISA-A) and imaging (UTC) outcome measures. Methods: In this study, 8 patients and 9 tendons (1 patient with bilateral tendons) with longstanding Achilles pain and 2D ultrasound and UTC findings of plantaris involvement were included. All patients had failed a conservative rehabilitation program. The surgical procedures were performed under local anaesthetic and involved excision of the plantaris tendon located medial to Achilles midportion and scraping of the ventral surface of the Achilles tendon (Figure 1 ). VISA-A questionnaire and UTC were performed pre- and 6 months post-surgery. UTC was performed on all tendons from calcaneal insertion to musculotendinous junction. Results: Seven out of eight patients were satisfied with the procedure. Mean Visa-A score pre-surgery was 56.8 (range from 34 to 73) and 6 months post-surgery was 93.3 (range from 87 to 100). There was a statistically significant increase in mean VISA-A scores after 6 months (t = 1.89, p < 0.001). UTC demonstrated a statistically significant increase in mean organised echopixels (type I+II) from 83.3 to 93.3 (t = 5.40 p < 0.001) and decrease in mean disorganised echopixels (type III+IV) from 16.7 to 6.7 (t = 5.40, p < 0.001) (Figure 2 and Figure 3 ). Conclusion: Excision of plantaris tendon in chronic midportion tendinopathy results in improved tendon matrix integrity on UTC. Improvements in tendon structure after plantaris excision could suggest a possible compression mechanism as the main causation for plantaris-associated Achilles tendinopathy. References: Van Sterkenburg, et al . J Anat. 2011;218:336–341 Sprang, et al . Histol Histopath . 2013;28:623–632 Van Schie, et al . Br J Sports Med. 2010;44:1153–1159 Alfredson, et al . Br J Sports Med. 2011;45:407–410 Rosengarten, et al . Br J Sports Med. 2015. [Epub ahead of print]